Improving Students' Quran Reading Skills through the At-Tanzil Method at Malaysian School - Yusriah Nabil Latifah; Nurul Iman; Syamsul Arifin (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2026)
The level of ability to read the Qur'an properly and correctly among students is currently an important issue for educational institutions. This research is urgent to find a structured way to overcome the difficulties of makhraj and tajweed that students often experience. This research aims to examine the application of the At-Tanzil method and assess its success rate in improving students' skills in reading the Qur'an. In addition, this study examines various factors that serve as both supporters and obstacles to the implementation of the At-Tanzil method, to improve the quality of the learning process for reading the Qur'an. This research will be carried out using a qualitative case study design in 2025 at SB At-Tanzil, Lembah Jaya, Selangor, Malaysia. The information collection process is carried out through observation, interviews, and documentation, and the data are then processed using an interactive model analysis, which includes the stages of data collection, data presentation, data reduction, and data conclusions. Based on the study's results, students' ability to read the Qur'an has increased significantly after participating in learning using the At-Tanzil method. The increase can be seen from the accuracy of the pronunciation of hijaiyah letters, the application of the tajweed law, and the fluency in reading the verses of the Qur'an. The gradual, step-by-step learning, starting from the basics and conveyed clearly and without hurry, is an important factor in the success of the At-Tanzil method. Some obstacles to applying the At-Tanzil method include the requirement that teachers attend training before teaching it. This is to ensure the learning process runs effectively and in a directed manner.